Vystavka meditsinskogo oborudovaniia . Vystavka meditsinskogo oborudovaniia . Exhibition of Medical Equipment . Выставка медицинского оборудования - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Comparative analysis of surgical instruments made in the Soviet Union and other countries. Featured in the program: Leonov, Boris Ivanovich (Director of the Institute of Medical Technology) Сравнительный анализ медицинских инструментов, выпущенных в СССР и в других странах мира. В программе участвуют: Леонов, Борис Иванович (Директор института медицинской техники)